The Taming of desire Unspecific postponement reduces desire for and consumption of postponed temptations. [article]. - Mead, Nicole L.
The present investigation began with the conjecture that people may do better by saying "some other time" instead of 'no, not ever" in response to temptations. Drawing from learning theories, we hypothesized that people interpret unspecific postponement ("I can have it some other time") as a signal that they do not strongly value the postponed temptation. In this way, unspecific postponement my reduce desire for and consumption of postponed temptations, both in the present moment and over time. Four experiments tested those hypotheses. A multiphase study using the free-choice paradigm supported the learning account for the effects of postponement: unspecific postponement reduced the immediate desire for a self-selected temptation which in turn statistically accounted for diminished consumption during the week after the manipulation-but only when postponement was induced, not when it was imposed (Experiment 1). Supporting the hypothesis that unspecific but not specific postponement connotes weak valuation, only unspecific postponement reduced attention to (Experiment 2) and consumption of (Experiment 3) the postponed temptation. Additionally, unspecific postponement delayed consumption primarily among those who were highly motivated to forgo consumption of the temptation (Experiment 3). A final multiphase experiment compared the effectiveness of unspecific postponement to the classic self-control mechanism of restraint, finding that unspecific postponement (vs. restraint) reduced consumption of the temptation in the heat of the moment and across 1 week post manipulation (Experiment 4). The current research provides novel insight into self-control facilitation, the modification of desire, and the differential effects of unspecific and specific intentions for reducing unwanted behavior. - (from the authors)
Keywords: Patrick, Vanessa M; Desire; Self-control.; Self-perception.; Consumption; Postponement